Pengaruh Struktur Modal dan Profitabilitas Terhadap Nilai Perusahaan Pada PT. Kalbe Farma, Tbk. - Muhibah Muhibah; Andi Rifqah Purnama Alam (AkMen JURNAL ILMIAH, 2021)
This study aims to determine the effect of capital structure (DER) and profitability (ROA) on firm value (PBV) at PT. Kalbe Farma, Tbk This research uses qualitative data and quantitative data. The data source used is secondary data. The analytical method used is multiple regression analysis, correlation coefficient (r) and coefficient of determination (r2), t-test and f-test. The results show that partially capital structure (DER) has a negative and insignificant effect on firm value, ( PBV) while profitability (ROA) has a positive and insignificant effect on firm value (PBV). Simultaneously, capital structure (DER) and profitability have no significant effect on firm value (PBV). Based on the results of the coefficient of determination of 0.36, it means that the firm value (PBV) is influenced by capital structure (DER) and profitability (ROA) by 36% and the remaining 64% is influenced by other factors not examined. The hypothesis in this study is accepted.